Characterization and performance evaluation of ammonia as fuel for solid oxide fuel cells with Ni/YSZ anodes. (1st March 2019) - Stoeckl, Bernhard; Subotić, Vanja; Preininger, Michael; Schwaiger, Marcel; Evic, Nikola; Schroettner, Hartmuth; Hochenauer, Christoph
Abstract: Ammonia appears to be a promising fuel for solid oxide fuel cell systems: it is a carbon-free species, can be stored easily and offers an excellent energy density with a high hydrogen content. This work shows comprehensive investigations of the direct operation of ammonia on an industrial-sized solid oxide fuel cell with Ni/YSZ anode. In the course of this study, ammonia exhibited excellent performance as a fuel for solid oxide fuel cells, although test results equivalent to those of hydrogen/nitrogen fuel mixtures were not attained. Electrochemical impedance spectroscopy proved the reduced performance output of ammonia as fuel to result from its endothermic decomposition. This significantly increased the ohmic resistance, which is mainly influenced by the ammonia flow rate. Operation in counter-flow is more favorable than in co-flow, as lower ohmic and diffusion resistances were measured. Twenty-four-hour stability tests showed stable behavior at 800 °C and a voltage decrease of 2% at 700 °C. Investigations of the anode micro-structure suggest that nickel nitriding occurred, as microscopic pores, particle enlargements, and agglomerations were identified at the metallic parts. Highlights: Measurements of SOFC anode temperature distribution during NH3 purging. Identification of the fuel inlet as catalytic active region for NH3 decomposition. NH3 decomposition improves in polarized conditions. Counter-flow is more favorable than co-flow for direct NH3 SOFC operation. NH3 purging results in micro-structural deformations of Ni/YSZ anodes.